2008
DOI: 10.1002/eji.200737954
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Toll‐like receptor 2 in mouse macrophages infected with Mycobacterium avium induces non‐oxidative and TNF‐independent anti‐mycobacterial activity

Abstract: Toll-like receptor (TLR) 2 plays an important role in the immune response to mycobacterial infections, being required for optimal immunity against certain virulent Mycobacterium avium strains. Here we analyzed the role of TLR2 in the intra-macrophagic growth of M. avium, using macrophages from TLR2-deficient mice. We found that the engagement of TLR2/TLR6 and/or TLR2/TLR1 receptors induced bacteriostasis of M. avium inside bone marrow-derived macrophages in a MyD88-dependent way. Additionally, lipoproteins fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…Meanwhile, the presence of both factors seems to be required for optimal antimicrobial activity. Therefore, human CD23 pathway differs from TLR-mediated antimycobacterial activity in mice (19), where the role of oxidative radicals and TNF-␣ is marginal.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the presence of both factors seems to be required for optimal antimicrobial activity. Therefore, human CD23 pathway differs from TLR-mediated antimycobacterial activity in mice (19), where the role of oxidative radicals and TNF-␣ is marginal.…”
Section: Discussionmentioning
confidence: 99%
“…TLR-2 activation results in the killing of M. tuberculosis by NO-dependent mechanisms [28] and in bacteriostasis of M. avium [29] by mechanisms that remain elusive. Here, we found that TLR-2 engagement leads to H-ferritin increase, which may contribute to the anti-mycobacterial activity induced by TLR-2 engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse bone marrow derived macrophages (mBMDM) were derived from bone marrow of femurs from 4-to 12-week-old C57BL/6 male mice, as previously described (26), and used at day 10 when fully differentiated. Sea bass peritoneal leukocytes (sbPL) were obtained from peritoneal cavities of sea bass, as previously described (27), and used at a density of 2 ϫ 10 6 cells/ml.…”
mentioning
confidence: 99%